1996
DOI: 10.1016/0031-9422(95)00600-1
|View full text |Cite
|
Sign up to set email alerts
|

Two sesquilignans from the wood of Abies marocana

Abstract: Abstract--From the chloroform extract of the wood of Abies rnarocana, consisting mainly of lignans, the acetoxyl derivatives of the new sesquilignans, 4,4",7",9,9"-pentahydroxy-3,3',3"-trimethoxy-4',8":7,9 were isolated; the trivial names, sesquimarocanols A and B, were subsequently assigned, respectively. Also, (9'R)-9'-hydroxylariciresinol tetraacetate, (7'R)-7'-hydroxylariciresinoi tetraacetate and sesquipinsapol B pentaacetate, which had previously only been found in A. pinsapo, were isolated, together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…NMR data on Ia was obtained on a pure isolated compound, while Ib and Ic were analysed as a mixture. The spectrometric and spectroscopic data on compound III were similar to those reported by Yoshikawa et al (1995), and compound II had data closely related to the acetylated compound reported by Barrero et al (1996). NMR data on the guaiacylglycerol moiety in all compounds were in accordance with those reported for threo-isomers (e.g., Yoshikawa et al 1995;Barrero et al 1996).…”
Section: Sesquilignans In Spruce Knotssupporting
confidence: 79%
See 1 more Smart Citation
“…NMR data on Ia was obtained on a pure isolated compound, while Ib and Ic were analysed as a mixture. The spectrometric and spectroscopic data on compound III were similar to those reported by Yoshikawa et al (1995), and compound II had data closely related to the acetylated compound reported by Barrero et al (1996). NMR data on the guaiacylglycerol moiety in all compounds were in accordance with those reported for threo-isomers (e.g., Yoshikawa et al 1995;Barrero et al 1996).…”
Section: Sesquilignans In Spruce Knotssupporting
confidence: 79%
“…Oligolignans have earlier been found in small amounts in Abies marocana, Abies pinsapo, Abies sachalinensis, and Tsuga heterophylla stemwood (Ozawa and Sasaya 1991;Barrero et al 1993Barrero et al , 1994Barrero et al , 1996Kawamura et al 1997), Araucaria angustifolia knots (Anderegg and Rowe 1974), Ehretia ovalifolia bark (Yoshikawa et al 1995), and Taxus mairei twigs (Yang et al 1999). Similar substances have also been found in plants such as Saururus cernuus, Saururus chinensis, Cerbera manghas, Cerbera odollam, and Arctium lappa (Ichihara et al 1976(Ichihara et al , 1977Rao and Alvarez 1983;Abe et al 1988a,b;Wang and Yang 1993;Han et al 1994;Sung et al 2001).…”
Section: Introductionmentioning
confidence: 98%
“…In certain families, such as the Pinaceae, they also typically help determine the characteristic color and properties of heartwood tissue. For example, over the last two decades, a range of dimeric and oligomeric lignans have been reported in the Pinaceae (Sakakibara et al, 1987;Barrero et al, 1993Barrero et al, , 1996Kawamura et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Acetylated lignans and sesquineolignans have been isolated before as plant products [13][14][15][16]. However, analogous compounds showing a cis-relationship between their two methine -lactonic protons are very rare in nature [17].…”
Section: Resultsmentioning
confidence: 98%